Synthetic tuning of the quantum properties of open-shell radicaloids - Lombardi, F; Ma, J; Alexandropoulos, DI; Komber, H; Liu, J; Myers, WK; Feng, X; Bogani, L (Cell Press, 2021)
Open-shell molecular radicaloids could constitute the key to molecular quantum information and quantum sensing technologies. The effect of their morphology on the quantum properties is anyway unknown, hampering the development of synthetic strategies. Herein, we establish the links between morphology and quantum properties, using three related radicaloids based on meta-quinodimethane. We unravel the roles of the π-conjugated backbone and those of the side groups on the spin-flip and quantum coherence times. The temperature regions are identified where different structural parts of the molecule or solvent become the dominant decoherence channel. The record quantum coherence values obtained at room temperature are still well below the intrinsic limits of radicaloids, and we discuss the directions to optimize the quantum performance.